Regulation of the calpain and ubiquitin proteasome systems in a canine model of muscular dystrophy - Wadosky, Kristine M. (2011)
INTRODUCTION: Previous studies have tested the hypothesis that calpain and/or proteasome inhibition is beneficial in Duchenne Muscular Dystrophy, based largely on evidence that calpain and proteasome activities are enhanced in the mdx mouse. METHODS: mRNA expression of ubiquitin proteasome and calpain system components were determined using RT-PCR in skeletal muscle and heart in the golden retriever muscular dystrophy model. Similarly, calpain 1/2 and proteasome activities were determined using fluorometric activity assays. RESULTS: We found that less than half of the muscles tested had increases in proteasome activity, and only one-half had increased calpain activity. Additionally, transcriptional regulation of the ubiquitin proteasome system was most pronounced in the heart, where numerous components were significantly decreased. DISCUSSION: This study illustrates the diversity of expression and activities of the ubiquitin proteasome and calpain systems, which may lead to unexpected consequences in response to pharmacologic inhibition.